ENHANCED ADSORPTION OF PHENOL USING ALKALINE MODIFIED ACTIVATED CARBON PREPARED FROM OLIVE STONES - Soudani Nouha; Najar-Souissi Souad; Ouederni Abdelmottalab (Journal of the Chilean Chemical Society, 2019)
Activated carbon (AC) prepared from olive stone (OSAC) was modified separately by ammoniac (OSAC/AM) and sodium hydroxide (OSAC/H) aqueous solutions impregnation in order to improve their adsorption properties toward phenol. The raw and modified activated carbons were characterized. The porous structure was characterized using N2 adsorption at 77 K. The surface functional group characteristics were examined by Fourier transform infrared (FTIR) spectroscopy, Boehm titration, the point of zero charge (pHpzc) measurement and X-ray photoelectron spectroscopy (XPS) method. The isotherms of phenol adsorption on the original and modified ACs were measured. After modification, the activated carbon showed enhanced adsorption capacity for phenol. The effect of alkaline solution concentration on adsorption process was investigated. Results showed a decrease of the microporosity of AC after alkalin treatment especially for higher solution concentration. The amounts of the surface basic groups of the modified ACs increased, in comparison with the original AC, with the increase of the alkaline concentration; however the acidic surface groups decreased. The equilibrium adsorption data were best described by Langmuir model. The maximum adsorption capacity of phenol enhanced for ammonia and sodium hydroxide, respectively, compared with the original AC. We noted that the higher alkaline concentration the higher the adsorption capacity of AC for phenol.